A case of antipsychotic-induced psychomotor seizure. Issue 3 (28th June 2022) - Zheng, Yanqun; Liu, Xiaohua; Ju, Mingliang
Abstract : A seizure is one of the most uncommon severe adverse side effects of antipsychotics. Clinical recognition rates for it are low, especially for psychomotor seizures. The authors present a case of psychomotor seizure caused by amisulpride to treat schizophrenia. A 60-year-old male patient in our hospital experienced a recent onset of repetitive, stereotyped involuntary and unconscious movements that began with amisulpride use. All of the symptoms disappeared following amisulpride withdrawal. His Naranjo Adverse Drug Reactions Probability Scale Score was 5 points. The case sheds light on the clinical risk of seizures related to antipsychotics.